1999
DOI: 10.1006/viro.1999.9963
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression from the ORF50/K8 Region of Kaposi's Sarcoma-Associated Herpesvirus

Abstract: The ORF50 gene of Kaposi's sarcoma (KS)-associated herpesvirus, or human herpesvirus 8 (KSHV), activates viral replication and is weakly homologous to the herpesvirus family of R transactivators; therefore, the transcription and translation events from this region of KSHV are key events in viral reactivation. We demonstrate that ORF50 is expressed in a bicistronic message after induction of the viral lytic cycle. ORF50 migrated as a series of polypeptides: the major ones as 119 and 101 kDa, respectively. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 44 publications
0
56
1
Order By: Relevance
“…The levels of RTA activation varied based on the cell type (BCBL-1, 144-fold; 293 T, 40-fold), but was independent of the presence of viral or B-cell factors for induction. The reported levels of expression contrast with the modest values for RTA-autoactivation previously reported by Seaman et al (1999) (2.7-fold) in BCBL-1 cells. It has been suggested that differences in the assay methodologies and in the length of the promoter sequence employed (Seaman et al used a 655 bp fragment) could be responsible for these discrepancies.…”
Section: The Autoregulation Of Rta Expressioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The levels of RTA activation varied based on the cell type (BCBL-1, 144-fold; 293 T, 40-fold), but was independent of the presence of viral or B-cell factors for induction. The reported levels of expression contrast with the modest values for RTA-autoactivation previously reported by Seaman et al (1999) (2.7-fold) in BCBL-1 cells. It has been suggested that differences in the assay methodologies and in the length of the promoter sequence employed (Seaman et al used a 655 bp fragment) could be responsible for these discrepancies.…”
Section: The Autoregulation Of Rta Expressioncontrasting
confidence: 99%
“…This protein, RTA DNA-binding domain (RDBD), has been particularly useful in defining promoter interactions of RTA that inhibited ORF50 function (Lukac et al, 1999). The activation domain is located at the carboxyl terminus of the protein, this region is highly acidic (aa 486-691) and contains numerous charged amino acids (Lukac et al, 1999;Seaman et al, 1999). This region also contains four repeated units of a highly hydrophobic domain, known as activation domains 1-4 (AD1-AD4), with sequence homology to other transcriptional factors such as VP16 domain A (Lukac et al, 1999).…”
Section: The Rta Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, KSHV RTA also acts to promote transcriptional activation of a variety of viral promoters, including those for delayed-early viral genes like TK, SSB, the posttranscriptional activator MTA, and the noncoding polyadenylated nuclear RNA, PAN (Lukac et al 1998). KSHV RTA contains an N-terminal DNA-binding domain and a C-terminal activation domain (Lukac et al 1998(Lukac et al , 2001Seaman et al 1999), and direct, high-affinity binding of purified, recombinant RTA to a site in the PAN promoter has been reported (Song et al 2001). However, other sites that are activated by RTA in vivo-for example, those in the MTA and RAP (K8, K-bZIP) promoters-display no homology to the PAN promoter site, raising the question of whether RTA might have other modes of DNA interaction, such as binding to cellular DNA binding factors.…”
mentioning
confidence: 99%
“…The mechanisms by which KSHV RTA acts have been extensively studied in cells transiently transfected by reporter gene constructs. RTA harbors a potent C-terminal activation domain, deletion of which results in a loss of transactivation activity (22,24). In addition, it has an N-terminal DNA-binding motif that can mediate sequence-specific DNA binding, and high-affinity sites for RTA recognition have been identified in several delayed-early promoters (25-27).…”
mentioning
confidence: 99%